2019
DOI: 10.1155/2019/2543413
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Differences between Traditional Chinese Medicine Syndromes in NYHA I–IV Classification of Chronic Heart Failure

Abstract: Objectives. This study investigated the distribution of characteristics of traditional Chinese medicine syndromes and their association with symptoms in 1027 patients with chronic heart failure (CHF). Methods. An observational study was performed by researchers, collecting data from 1036 patients with CHF from 24 Chinese medicine hospitals from May 2009 to December 2014. Due to incomplete information from nine patients, 1027 patients with CHF were analysed. The distribution of syndromes in CHF and association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…TCM has accumulated a lot of experience in the treatment of cardiovascular diseases and believes that heart yang deficiency is the root of heart failure. Heart failure has gradually evolved from heart qi insufficiency to heart yang deficiency, which is caused by the weakness of heart qi and yang, and runs through the whole process of disease occurrence and development [ 12 ]. Although Western medicine has made significant progress in CHF treatment, there are still many shortcomings, such as the side effects of drugs which lead to malignant arrhythmia, affecting the therapeutic effect [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…TCM has accumulated a lot of experience in the treatment of cardiovascular diseases and believes that heart yang deficiency is the root of heart failure. Heart failure has gradually evolved from heart qi insufficiency to heart yang deficiency, which is caused by the weakness of heart qi and yang, and runs through the whole process of disease occurrence and development [ 12 ]. Although Western medicine has made significant progress in CHF treatment, there are still many shortcomings, such as the side effects of drugs which lead to malignant arrhythmia, affecting the therapeutic effect [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we focused on the clinical risks of ischemic stroke and demonstrated that a history of insomnia or drinking could indicate the presence the two TCM syndromes, QDBS and PSIC. Shi [35] found that Qi deficiency was diagnosed in 87.43% of patients with insomnia and spiritlessness. is finding coincides with our result that patients of ischemic stroke with QDBS syndrome were more likely to manifest insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Homeostatic imbalance is directly involved in the various processes required for the progression of heart failure: oxidative stress, inflammation, cardiac hypertrophy, cell death, and tissue fibrosis. Multiple clinical investigations of hospitalized patients have found that elderly patients (average age about 73 years) with heart failure and kidney-Yang deficiency have higher plasma AngII level, slightly lower left ventricular ejection fraction (EF) and fractional shortening (FS), and much lower left ventricular diastolic function (E/A ratio) than heart failure patients with non-kidney-Yang deficiency ( 2 , 5 , 134 ). Moreover, patients with kidney-Yang deficiency are mostly distributed in NYHA class III and IV, and non-kidney-Yang deficiency exists in NYHA class II ( 2 , 5 , 134 ).…”
Section: Effect Of Prescriptions On Changes Of Sympathetic Excitabili...mentioning
confidence: 99%
“…According to the combination of different traditional Chinese medicine (TCM) syndrome elements, TCM can divide chronic heart failure into 4–6 TCM syndromes ( 1 ), which are mainly related to deficiency of heart and kidney yang and heart qi deficiency. The report of Shi et al ( 2 ) compared the main TCM syndromes of chronic heart failure with the New York Heart Association (NYHA) classification, and found that there is a certain correlation between NYHA classification and the distribution of heart-kidney yang deficiency and heart-qi deficiency. Heart-qi deficiency is basically concentrated in categories I and II, and the frequency of kidney yang deficiency and body fluid retention in class III+IV is higher than that in class I and II.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation